Ceacal perforation in a premature newborn infant complicating milk curd syndrome: Case report - Aytaç KARKINER; Günyüz TEMİR; Münevver HOŞGÖR; Cüneyt GÜNŞAR; İrfan KARACA (Turkish Journal of Gastroenterology, 2019)
-